A study of digital divide under the platform model development in the corporate sector of the economy - Andrey E. Plakhin; Valery Zh. Dubrovsky; Ekaterina S. Ogorodnikova (Journal of New Economy)
The existence of digital divide significantly hinders the development of a platform model in the corporate sector of the Russian economy, which in turn does not contribute to the active manifestation of the positive effects of digitalisation. The lack of methodological and empirical works describing digital divide in the corporate sector of the economy does not allow devising effective methods of solving this problem. The purpose of the article is to assess the digital divide that impede the establishment of a platform model in the corporate sector of the national economy. The research methodology is based on the theory of innovation, the concept of technological paradigm, and the concept of the fourth industrial revolution that substantiate the advantages of digitalisation and explain economic growth from the perspective of technological progress. The main method is correlation analysis, which is performed on groups of indicators characterising the use of platform technologies by organisations and reflecting a number of other factors. The data on the use of software and digital technologies in organisations over the years from 2012 to 2022 is taken from the HSE University statistical publications. The findings allow concluding that the greatest importance for the development of a platform model in the corporate sector of the economy is held by the homogeneity of digital technologies used within an industry. The second important factor is the homogeneity in the use of software focused on the interaction with partners and the functioning of organisations in terms of access to broadband internet. The results obtained allow diagnosing the formation of a platform model by describing the digital and software technologies used by potential participants of digital platforms and business ecosystems.